The effect of financial performance and corporate governance on tax avoidance with environmental performance as a moderator - Martiningsih, Sri; Lastanti, Hexana Sri (Educoretax, 2025)
This study aims to examine the influence of financial performance and corporate governance on tax avoidance, with environmental performance acting as a moderating variable. Tax avoidance is designated as the dependent variable, while profitability (ROA), managerial ownership, the composition of independent commissioners, and auditor quality are regarded as independent variables. Corporate Social Responsibility (CSR) is recognized as both an indicator of environmental performance and a moderating variable. The study employs a quantitative methodology utilizing purposive sampling, focusing on banking entities listed on the Indonesia Stock Exchange (IDX) during the period from 2021 to 2023. Data analysis is executed through multiple regression, T-tests, and F-tests using SPSS Version 25. The findings reveal that financial performance (profitability) and environmental performance (CSR) exert a significant negative impact on tax avoidance. Furthermore, CSR enhances the effect of profitability on tax avoidance. Conversely, managerial ownership, the size of the independent board of commissioners, and auditor quality do not exhibit a significant influence on tax avoidance. The research also indicates that environmental performance does not moderate the effects of managerial ownership, the size of the independent board of commissioners, and auditor quality on tax avoidance. The implications of this study highlight the necessity of integrating CSR into business strategies to foster ethical tax practices. These findings contribute to the broader discourse on tax compliance and corporate governance, offering valuable insights for stakeholders aiming to reconcile financial goals with social responsibilities.